Sistem Pendukung Keputusan Penentuan Lokasi dan Pemetaan Secara Simultan dengan OLAP - Pradhana, Harindra W; Suryono, Suryono; Widodo, Achmad (JSINBIS (Jurnal Sistem Informasi Bisnis), 2013)
This research proposes simultaneous localization and mapping (SLAM) system processed separately from the robot using data ware house. Information in the data warehouse processed separately to allow complex computation held without lowering robotic system performance. The system helps making decision by analyzing information in the data warehouse. Decision support information visualized in vector graphics to helps robotic information interpretation. This system use online analytical processing (OLAP) on processing and analyzing information in the data warehouse. Visualization process use SVG to display map from robotic data processing. Web server manages all of the processing and analysis of OLAP information and displays it through browser to the user. This research produces interactive and informative decision support system. The web server quickly process information and displays it to the browser. System processing and analysis generates relevant information with low error. For further research, conventional SLAM methods can be added to the server to operate the information in the data warehouse.